2015
DOI: 10.37190/epe150308
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and numerical experiments into efficient management of VDR filter plants

Abstract: One of the operation rules of variable declining rate (VDR) filters states that the longest filtration runs are achieved when the highest flow through the most recently backwashed filter and the highest available head loss coincide. This rule has previously been published by Dąbrowski, who used a simplified mathematical model of VDR filters developed by Di Bernardo. However, until now no experimental verification of this optimisation approach has been presented. A series of tests were carried out on a laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…However, according to the calculations, a slightly better filtrate was obtained in the system with a constant filtration rate, when the filter cycles were of the same length [43]. First, theoretically [47], and then experimentally [48], it has been shown that in the case of filter plants controlled by variable declining rate operation systems, in comparison with constant rate systems, longer filter cycles, and thus saving water for backwashing, are achieved in the VDRF operation systems if the ratio of the hydraulic load of the most recently backwashed filter to the average hydraulic load of the all filters in the plant is higher than 1.2. This VDR system can be used for the time-varying turbidity of raw water [49,50], but it requires adjustment when changing the water temperature and it is troublesome to use this system in large stations due to small fluctuations in the water table above the filters, which makes it difficult to determine the appropriate time of subsequent backwashing in stations [51].…”
Section: Discussionmentioning
confidence: 99%
“…However, according to the calculations, a slightly better filtrate was obtained in the system with a constant filtration rate, when the filter cycles were of the same length [43]. First, theoretically [47], and then experimentally [48], it has been shown that in the case of filter plants controlled by variable declining rate operation systems, in comparison with constant rate systems, longer filter cycles, and thus saving water for backwashing, are achieved in the VDRF operation systems if the ratio of the hydraulic load of the most recently backwashed filter to the average hydraulic load of the all filters in the plant is higher than 1.2. This VDR system can be used for the time-varying turbidity of raw water [49,50], but it requires adjustment when changing the water temperature and it is troublesome to use this system in large stations due to small fluctuations in the water table above the filters, which makes it difficult to determine the appropriate time of subsequent backwashing in stations [51].…”
Section: Discussionmentioning
confidence: 99%